Physical oceanography from ALKOR cruise AL561 (02.08.- 13.08.2021, Skagerrak) - Schmidt, Mark (PANGAEA, 2025)
A CTD system was used on AL561-cruise (02.08.- 13.08.2021, Schmidt et al., 2021), to study oceanographic characteristics of the water column in the Skagerrak. The CTD (Sea-Bird Electronics, SBE9plus) was a real-time data acquisition system transmitting data via coaxial cable to the deck unit (SBE11plus). The CTD rosette was equipped with an additional sensor for turbidity/fluorescence.
Keywords: CTD; oceanography; Skagerrak